Membrane-assisted reactor for the direct conversion of CO2 to DME/MeOH - Francesco Frusteri; Giuseppe Bonura; Catia Cannilla; Serena Todaro; Alessandro Cajumi (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2022)
Several strategies are currently underway to investigate alternative routes to efficiently use CO2 as a carbon source for the production of alternative fuels for energy end transportation [1,2].